Konsep Transformasi Struktural Pada Sektor Industri - Eki Indriyanti; Melkior Keleka Hayon; Muhammad Yasin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Structural transformation is a process of transition from traditional economic system to modern economic system. Structural transformation is characterized by a shift in labor and investment from the primary sector to the secondary sector and the latter to the tertiary sector. Economic growth accompanied by structural transformation can be achieved by: (1) increasing productivity in each sector and (2) shifting labor from low-productivity to high-productivity sectors. One of the primary sectors in Indonesia is agriculture. Agriculture is an important sector for Indonesia. Indonesia is a country that is undergoing structural transformation the structural transformation of the economy generally from traditional agriculture to the agro-industrial sector and the non-agricultural sector (agribusiness) that creates higher added value (BPS, 2015)